1972
DOI: 10.1901/jeab.1972.18-147
|View full text |Cite
|
Sign up to set email alerts
|

IN COMPATABILITY BETWEEN THE PIGEONS' UNCONDITIONED RESPONSE TO SHOCK AND THE CONDITIONED KEY‐PECK RESPONSE1

Abstract: High-speed photography was used to compare the pigeon's response to unsignalled shock with the pigeon's key-peck response. During shock, pigeons flex their neck (i.e., the distance between their eyes and shoulders decreases). Following shock, the neck is extended. During key pecking, the neck remains extended and the head moves toward the key in a slight arc as though attached to a fixed fulcrum. Response topography during pecking and shock appear to be incompatible, and it is concluded that the difficulty in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…That is, the running response rate increased for the first several responses after shock. This observation is consistent with a previous study which demonstrated that shock-elicited behavior which is incompatible with key-peck responding diminishes within a short time after shock presentation (Smith, Gustavson, & Gregor, 1972).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…That is, the running response rate increased for the first several responses after shock. This observation is consistent with a previous study which demonstrated that shock-elicited behavior which is incompatible with key-peck responding diminishes within a short time after shock presentation (Smith, Gustavson, & Gregor, 1972).…”
Section: Discussionsupporting
confidence: 93%
“…It is clear that shock may elicit behavior that is incompatible with punished responding (e.g., Fowler & Miller, 1963;Smith et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Key pecking would be incompatible with the unconditioned response elicited by shock. Smith, Gustavson, and Gregor (1972) presented data in support of this view, giving more weight to Bolles' (1970) species-specific defense theory of escape and avoidance behavior.…”
mentioning
confidence: 73%
“…Whether this results, however, from pecking being a low-probability SSDR or from competition between the required operant response and neck contraction elicited by shock presentation (cf. Smith, Gustavson, & Gregor, 1972) is not readily apparent in the absence of a comparative database involving a variety of species, responses, and aversive stimuli. Pecking under timeout postponement is of interest in this regard because it provides one such comparative analysis of species and response generality (Sidman, 1960) and utilizes an aversive stimulus other than electric shock.…”
Section: Discussionmentioning
confidence: 99%